PENGARUH PEMBERIAN POC AIR CUCIAN BERAS PADA PERTUMBUHAN VEGETATIF TANAMAN CABAI MERAH (Capsicum annuum spp) - Wahyuni, Sri; Sepriani, Yusmaidar; Sitanggang, Kamsia Dorliana; Triyanto, Yudi (Agros Journal of Agriculture Science, 2024)
Red chili (Capsicum annuum spp.) is a vegetable plant that has long been cultivated in Indonesia because of its high level of adaptability. As a result, almost anywhere can support the cultivation of this plant. Therefore, efforts need to be made to increase the production of red chili plants, including by using organic fertilizer made from rice washing waste, in order to meet the plant's nutrient needs. The aim of this research is to determine the effect of applying Organic Liquid Compost (OLC) made from rice washing water on the development of red chili plants, especially when using high observation parameters. plants, number of leaves, and stem diameter. The implementation of this research began from January to March 2024 in Perjuangan Indah Hamlet, West Bilah District, Labuhanbatu Regency. This research used a factorial Randomized Block Design (RBD) with a single component, namely POC fertilizer from rice washing water, which had four levels, namely P0 as control, P1 as much as 200 ml per plant, P2 as much as 250 ml per plant, and P3 as much as 300 ml. ml per plant. Based on the research results, it is known that giving OLC rice washing water at a dose of P3: 300 ml/plant has an effect on height. plants, number of leaves, and stem diameter of red chili plants.Based on the research results, it is known that the stem diameter, number of leaves, and plant height of red chili plants are all influenced by the application of OLC washing rice at a rate of P3: 300 ml/plant. Keywords: rice washing water OLC; red chili INTISARIUsaha untuk meningkatkan produksi tanaman cabai merah salah satunya dilakukan dengan pemberian pupuk organik yang dihasilkan dari limbah pencucian beras. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian Pupuk Organik Cair (POC) dari air cucian beras terhadap pertumbuhan vegetatif tanaman cabai merah. Penelitian dialkukan pada bulan Januari sampai Maret 2024 di Dusun Perjuangan Indah Kecamatan Bilah Barat, Kabupaten Labuhanbatu. Penelitian menggunakan Rancangan Acak Kelompok (RAK) faktorial dengan komponen tunggal, yaitu pupuk POC air cucian beras, yang mempunyai empat taraf yaitu P0 (kontrol), P1 (200 ml per tanaman), P2 (250 ml per tanaman), dan P3 (300 ml per tanaman). Parameter yang diamati adalah tinggi. tanaman, jumlah daun, dan diameter batang. Berdasarkan hasil penelitian diketahui bahwa pemberian POC air cucian beras dengan takaran P3: 300 ml/tanaman.berpengaruh terhadap tinggi. tanaman, jumlah daun, dan diameter batang tanaman cabai merah. Kata kunci : cabai merah; poc air cucian beras